Physical and Mental Health Problems of Elderly People at Nagarjun Municipality in Kathmandu - Kunwar, Thaneshwar (Humanities and Social Sciences Journal, 2021)
Aging is a gradual, continuous process of natural change that begins in early adulthood. The objective of the study is to analyse the physical and mental health problems of elderly people in Nagarjun Municipality, Kathmandu. Ward number 6 is selected randomly among the 10 wards which has 680 elderly people aged 60+. Yamene formula (n=N/1+Ne2) was used to determine the sample size (n=250) and applied systematic random sampling method to select the samples. Data entry and analysis was done using SPSS version 21.0. The most prevalent chronic illness in this study was joint pain (67.20%), followed by Gastrointestinal (51.10%) and Hypertension or BP (39.60%). By using logistic regression analysis it shows that the variable of ownership of land certificate has the strongest net association with [OR=2.06(1.18-3.59)] and other variable involvement in the social and religious organization has the second strongest association with [OR=1.77(0.99-3.17)]. Study shows that elderly who do not have ownership of the land certificate have more than two times mental health problems than who have land certificate. Various health schemes, policies and programs can be designed in the research area and similar setting based on the study findings.